A Current and Evolving Treatment Landscape on Esophageal Cancer - Nicole B. Balmaceda; Joaquina C. Baranda; Peter DiPasco; Weijing Sun; John Ashcraft; Joseph Valentino; Mazin Al-Kasspooles (Highlights on Medicine and Medical Research Vol. 10, 2021)
With advances in state-of-the-art technology, trendy diagnostic and prognostic molecular markers, and cutting-edge surgical techniques, the overall survival for patients with many types of cancers has improved. However, there is a disconnect between esophageal cancer and the acceleration in cancer care seen in other malignancies. Based on data reported by Surveillance, Epidemiology, and End Results Program (SEER), the 5-year survival rate for patients with esophageal cancer is only 19.9% [1]. Poor prognosis is likely due to an overwhelming number of patients with advanced disease during the time of diagnosis, and is also reflective of the unsatisfactory outcomes from current treatments. In this article, we will review the epidemiology and the recently revised staging of esophageal and esophagogastric junction cancers. We will discuss the current roles of endoscopic resection, surgery, radiation therapy, and systemic therapy used individually, or as components of multimodality treatment. We will describe the changes in treatment landscape with targeted therapy and immunotherapy. The focus of clinical investigations continues to shift from the traditional empiric chemotherapy to more individualized treatments based on molecular oncology and use of immunotherapy. Further identification of prognostic values may help clarify the optimal approach to treatment and management for patients with esophageal cancer, and hopefully improve survival. Clinical trials investigating strategies in prevention, early diagnosis, and treatment of early and advanced disease are guided by lessons learned in epidemiology, molecular genetics, pharmacogenomics, and precision medicine.